Review of the Inca irroratus species group with description of two new species of Inca LePeletier & Serville, 1828 (Coleoptera, Scarabaeidae, Cetoniinae) - Sousa, Rafael; Seidel, Matthias (European Journal of Taxonomy, 2021)
The Brazilian endemic irroratus species group of the genus Inca (Scarabaeidae, Cetoniinae) is defined and described. This species group is composed of Inca irroratus Chevrolat, 1833 and two new species: I. axeli sp. nov. and I. neglectus sp. nov. One new synonym is proposed: I. irroratus Chevrolat, 1833 = I. burmeisteri Burmeister, 1844 syn. nov. To guarantee nomenclatural stability, a neotype is designated for I. irroratus and a lectotype for I. burmeisteri. A key to all species of Inca and a map with the distribution of the irroratus species group are provided.